Application of Blockchain in Agri-Food Supply Chain - Utkarsh Tiwari (Britain International for Academic Research (BIAR) Publisher, 2020)
Supply chain traceability is one of the most important problems faced by all organizations globally. Tracking any commodity is a tedious job and requires a lot of manual attention. The existing system uses a centralised database system to track a commodity. Blockchain is a decentralised, immutable ledger managed by a cluster of computers. The very nature of blockchain makes it suitable technology for traceability in a supply chain. Blockchain creates immutable records. Once a transaction is stored in the blockchain, it is impossible to tamper it illegally. This immutability of blockchain builds trust among the participants that conduct business in a lack of trust environment. Using consensus protocols, blockchain builds trust between the various participants. Blockchain provides traceability since immutable records are added in blockchain; it is easy to track the source of the product. This paper illustrates the Application of Blockchain in Agri-Food Supply Chain. It unfolds how blockchain technology can be integrated to an Agri Supply Chain and improves the traceability. This integration enables companies to quickly track unsafe products back to their source and see where else they have been distributed. This integration can result to prevent illness and save lives, as well as reduce the cost of product recalls.